2013
DOI: 10.1002/pits.21739
|View full text |Cite
|
Sign up to set email alerts
|

Personal and School Cultural Factors Associated With the Perceptions of Teachers’ Efficacy in Handling Student Misbehavior

Abstract: One approach for understanding teachers’ behavioral responses to classroom student misbehavior is through the perceptions of efficacy in handling this stressor. The present study investigated the relationship and predictive ability of personal and school cultural factors as they relate to perceptions of teachers’ efficacy in handling student misbehavior (TEHSM). Participants were 344 primary (n = 189) and secondary (n = 155), full‐time, public school teachers from a southeastern state in the USA. Teachers comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 64 publications
2
19
0
10
Order By: Relevance
“…More specifically, teachers' sense of efficacy is closely linked to teacher behaviors in the classroom (Ghaith & Yaghi, 1997;Guskey, 1988;Milner, 2002;Napoles & MacLeod, 2013;Önen & Kaygisiz, 2013), their ideology about classroom management (Woolfolk & Hoy, 1990), enthusiasm for teaching (Allinder, 1994;Ashton, 1984;Ashton & Webb, 1986), level of stress experienced in teaching (Smylie, 1988), burnout (Brouwers & Tomic, 2000;Oakes, Lane, Jenkins, & Booker, 2013), quality of teaching (Raudenbush, Bhumirat, & Kamali, 1992), use of alternative assessment (TaTar & Buldur, 2013), and job satisfaction (Caprara, Barbaranelli, Borgogni, & Steca, 2003;Caprara, Barbaranelli, Steca, & Malone, 2006). Teachers with higher levels of self-efficacy were less critical of students when they made errors (Ashton & Webb, 1986;Tsouloupas, Carson, & Matthews, 2014), less inclined to refer a difficult student to special education (Meijer & Foster, 1988;Podell & Soodak, 1993), and more willing to support and cope with students' Teaching Education 3 emotional and behavioral difficulties (Poulou & Norwich, 2002). Khoury-Kassabri (2012) examined 30 Arab schools across Israel and found that teachers with lower perception of their self-efficacy had higher support of the use of verbal or physical violence.…”
Section: Importance Of Teacher Efficacymentioning
confidence: 96%
“…More specifically, teachers' sense of efficacy is closely linked to teacher behaviors in the classroom (Ghaith & Yaghi, 1997;Guskey, 1988;Milner, 2002;Napoles & MacLeod, 2013;Önen & Kaygisiz, 2013), their ideology about classroom management (Woolfolk & Hoy, 1990), enthusiasm for teaching (Allinder, 1994;Ashton, 1984;Ashton & Webb, 1986), level of stress experienced in teaching (Smylie, 1988), burnout (Brouwers & Tomic, 2000;Oakes, Lane, Jenkins, & Booker, 2013), quality of teaching (Raudenbush, Bhumirat, & Kamali, 1992), use of alternative assessment (TaTar & Buldur, 2013), and job satisfaction (Caprara, Barbaranelli, Borgogni, & Steca, 2003;Caprara, Barbaranelli, Steca, & Malone, 2006). Teachers with higher levels of self-efficacy were less critical of students when they made errors (Ashton & Webb, 1986;Tsouloupas, Carson, & Matthews, 2014), less inclined to refer a difficult student to special education (Meijer & Foster, 1988;Podell & Soodak, 1993), and more willing to support and cope with students' Teaching Education 3 emotional and behavioral difficulties (Poulou & Norwich, 2002). Khoury-Kassabri (2012) examined 30 Arab schools across Israel and found that teachers with lower perception of their self-efficacy had higher support of the use of verbal or physical violence.…”
Section: Importance Of Teacher Efficacymentioning
confidence: 96%
“…In linea con la letteratura (e.g., Tsouloupas, Carson, & Matthews, 2014), ci aspettiamo che le modalità di gestione della classe, nei suoi vari aspetti, messe in atto dagli insegnanti predicano relazioni adeguate e soddisfacenti tra insegnanti e allievi (ipotesi 1). Questa ipotesi verrà testata considerando il punto di vista dell'osservatore esterno che può svolgere un ruolo di valutatore neutrale e quindi avere una percezione consensuale della gestione della classe.…”
Section: Obiettivio E Ipotesiunclassified
“…Molti studi si sono concentrati sul benessere scolastico inteso in termini di soddisfazione da parte degli studenti circa l'avere un insegnante con buone abilità specifiche nella trasmissione delle informazioni (e.g., Tian, Du, & Huebner, 2015;Onwuegbuzie, Witcher, Collins, Filer, Wiedmaier, & Moore, 2007;Zhang, 2004). Altri recenti studi suggeriscono che una relazione positiva fra insegnante e allievi risulta rilevante rispetto al grado di soddisfazione verso il docente e più in generale per la qualità della lezione, e pertanto tale relazione positiva influenza il grado di soddisfazione e la qualità della lezione stessa (e.g., Tsouloupas, Carson, & Matthews, 2014). In altre parole, diverse evidenze empiriche mostrano come sia centrale il ruolo delle buone prassi comunicative e sociali che l'insegnate può mettere in atto per favorire nei suoi allievi adeguati livelli di benessere scolastico.…”
Section: Introduzioneunclassified
“…Student misbehavior has been an ongoing issue for school and district leaders, and adapting the culture of the school climate is a growing concern (Tsouloupas et al, 2014). The implementation of PBIS has been shown to improve school climate and decrease student behavior (Ross & Horner, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Tsouloupas, Carson, and Matthews (2014) found teachers who considered themselves to be extroverts (engaged in social interaction) were more likely to rate themselves as having higher efficacy and were more likely to build a strong rapport with students in the classroom. Teachers who viewed themselves as having higher efficacy were likely to have better results in handling student misbehavior.…”
Section: Approaches To Disciplinementioning
confidence: 98%